2020
DOI: 10.2478/atd-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in English Language Teaching: Views from Turkey

Abstract: Introduction: Research into gender diversity and equality of gender in humanities has been mounting since 1960s, when post-modernism and post-structuralism emerged as a reaction to metanarratives of modernization. Methods and approaches in ELT also arose in the same years. However, queer and LGBT identities were intentionally ignored in ELT discipline and departments, although English as a lingua franca was already hailed in the inner circle. This study aimed to unearth the views of young adult learners of Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Many themes about equality between the sexes are presented in textbooks, curricula, and other educational resources yet are regarded as ineffective in capitalism. The pursuit of increased profits by capitalism harms LGBTQ persons (Ulum, 2020).…”
Section: Gendered Languagementioning
confidence: 99%
“…Many themes about equality between the sexes are presented in textbooks, curricula, and other educational resources yet are regarded as ineffective in capitalism. The pursuit of increased profits by capitalism harms LGBTQ persons (Ulum, 2020).…”
Section: Gendered Languagementioning
confidence: 99%
“…The first way to achieve this goal is including the Anthropocene or topics related to it in the curriculum. Yet, the literature review has showed that several studies have been conducted to evaluate the English language teaching curricula for lower secondary school (also known as middle school) prepared at different times in Turkey (Aksoy, 2020;Aktı Aslan & İzci, 2017;Arı, 2013;Demirtaş & Erdem, 2015;Dinçer & Koç, 2020;Dinçer & Saracalıoğlu, 2017;Kozikoğlu, 2014;Ordem & Ulum, 2020). These studies have generally focused on EL teachers' and students' ideas about the curriculum and have shown that the evaluated curricula have some strengths but need to be improved.…”
Section: Introductionmentioning
confidence: 99%